NT‐proBNP by Itself Predicts Death and Cardiovascular Events in High‐Risk Patients With Type 2 Diabetes Mellitus - Marcus V. B. Malachias; Pardeep S. Jhund; Brian L. Claggett; Magnus O. Wijkman; Rhonda Bentley‐Lewis; Nishi Chaturvedi; Akshay S. Desai; Steven M. Haffner; Hans‐Henrik Parving; Margaret F. Prescott; Scott D. Solomon; Dick De Zeeuw; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2020)
Background NT‐proBNP (N‐terminal pro‐B‐type natriuretic peptide) improves the discriminatory ability of risk‐prediction models in type 2 diabetes mellitus (T2DM) but is not yet used in clinical practice. We assessed the discriminatory strength of NT‐proBNP by itself for death and cardiovascular events in high‐risk patients with T2DM. Methods and Results Cox proportional hazards were used to create a base model formed by 20 variables. The discriminatory ability of the base model was compared with that of NT‐proBNP alone and with NT‐proBNP added, using C‐statistics. We studied 5509 patients (with complete data) of 8561 patients with T2DM and cardiovascular and/or chronic kidney disease who were enrolled in the ALTITUDE (Aliskiren in Type 2 Diabetes Using Cardiorenal Endpoints) trial. During a median 2.6‐year follow‐up period, 469 patients died and 768 had a cardiovascular composite outcome (cardiovascular death, resuscitated cardiac arrest, nonfatal myocardial infarction, stroke, or heart failure hospitalization). NT‐proBNP alone was as discriminatory as the base model for predicting death (C‐statistic, 0.745 versus 0.744, P=0.95) and the cardiovascular composite outcome (C‐statistic, 0.723 versus 0.731, P=0.37). When NT‐proBNP was added, it increased the predictive ability of the base model for death (C‐statistic, 0.779 versus 0.744, P<0.001) and for cardiovascular composite outcome (C‐statistic, 0.763 versus 0.731, P<0.001). Conclusions In high‐risk patients with T2DM, NT‐proBNP by itself demonstrated discriminatory ability similar to a multivariable model in predicting both death and cardiovascular events and should be considered for risk stratification. Registration URL: https://www.clini​caltr​ials.gov; Unique identifier: NCT00549757.